2020
DOI: 10.1007/s40262-020-00933-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Population Pharmacokinetics of Darunavir in SARS-CoV-2 Patients vs. HIV Patients: The Role of Interleukin-6

Abstract: Background Darunavir is an anti-HIV protease inhibitor repurposed for SARS-CoV-2 treatment. Objective The aim of this study was to assess the population pharmacokinetics of darunavir in SARS-CoV-2 patients compared with HIV patients. Methods Two separate models were created by means of a nonlinear mixed-effect approach. The influence of clinical covariates on each basic model was tested and the association of significant covariates with darunavir parameters was assessed at multivariate regression and classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…The 13 patients of the study had median CRP levels of > 170 U/l [ 57 ]. Another study reported a major difference in the median oral clearance (CL/F) of darunavir between COVID-19 patients with IL-6 > 18 pg/ml, patients with an IL-6 < 18 pg/ml, and HIV patients not infected with SARS-CoV-2 (2.78, 7.24, 9.75 l/h) [ 54 ]. However, no significant difference was observed in CL/F between patients with IL-6 < 18 pg/ml and HIV patients.…”
Section: Effect Of Inflammation On Cytochrome P450 Enzyme Expression mentioning
confidence: 99%
See 4 more Smart Citations
“…The 13 patients of the study had median CRP levels of > 170 U/l [ 57 ]. Another study reported a major difference in the median oral clearance (CL/F) of darunavir between COVID-19 patients with IL-6 > 18 pg/ml, patients with an IL-6 < 18 pg/ml, and HIV patients not infected with SARS-CoV-2 (2.78, 7.24, 9.75 l/h) [ 54 ]. However, no significant difference was observed in CL/F between patients with IL-6 < 18 pg/ml and HIV patients.…”
Section: Effect Of Inflammation On Cytochrome P450 Enzyme Expression mentioning
confidence: 99%
“…IL-6 was the only factor that was significantly correlated with CL/F. Other factors that were tested included age, body weight, BSA, serum creatinine, ALT, and AST levels, and concomitant hydroxychloroquine administration [ 54 ]. Similarly, plasma lopinavir concentrations were six times higher in COVID-19 patients (median CRP 186 mg/l) compared to HIV patients [ 55 ].…”
Section: Effect Of Inflammation On Cytochrome P450 Enzyme Expression mentioning
confidence: 99%
See 3 more Smart Citations